(untitled) (CIPEEX, 2022)
THE SORROWS OF YOUNG WERTHER: A MIMETICAL AND SOCIAL ANALYSIS OF LITERATURES &NBSP; ABSTRACT: THE PRESENT WORK CONCLUDES THE SUBJECT "TIME, MEMORY AND NARRATIVES" IN ORDER TO ARTICULATE THE ASPECTS ADDRESSED IN THE CLASSROOM, THE RESEARCH THEME AND INDIVIDUAL STUDIES. THEREFORE, THE FOLLOWING ARTICLE AIMS TO ANALYZE GOETHE’S WORK, €ŒTHE SORROWS OF YOUNG WERTHER€ FROM PAUL RICOEUR’S MIMESIS I, II AND III, AS WELL AS EXPLORE THE SOCIAL ASPECTS OF THE WORK. THE CHOICE WAS MADE SINCE THE THEME RESEARCHED IS ENTITLED €ŒSELF-MUTILATION AND SUICIDE IN ADOLESCENCE: A HISTORICAL-CULTURAL PERSPECTIVE OF THE PHENOMENON€. IT IS BELIEVED THAT THE LITERATURE EMBRACES MANY SUBJECTIVE ASPECTS OF MAN IN HIS HISTORICAL AND CULTURAL TIME, PROVIDING SUBSIDIES FOR A BETTER UNDERSTANDING OF THESE PHENOMENA THAT CROSS HUMANITY, SUCH AS SUICIDE. THUS, A NARRATIVE ANALYSIS OF THE TEXT AND UNVEILING OF THE SOCIAL CRITICISM BEHIND GOETHE’S WORK WAS DONE. KEY WORDS: WERTHER; SUICIDE; MIMESIS; GOETHE.